Examining peer support arrangements for students with visual impairment. (May 2022) - Tuttle, Michael; Carter, Erik W.
Students with visual impairment (VI) often have limited social interactions in inclusive classroom settings. This study used a multiple-probe-across-participants design to evaluate the impact of peer support arrangements on the social interactions of three students with VI in general education classes. Students experienced higher levels of peer interaction while participating in peer support arrangements while maintaining high levels of academic engagement during the intervention. Most students and teachers reported that peer support arrangements provided positive experiences, resulted in multiple benefits, and could be implemented feasibly and acceptably in inclusive classrooms. We offer recommendations for research and practice aimed at enhancing the quality of inclusive experiences for students with VI.